Soil Liquefaction and Other Seismic-Associated Phenomena in the City of Chone during the 2016 Earthquake of Coastal Ecuador - Eduardo Ortiz-Hernández; Kervin Chunga; Theofilos Toulkeridis; José Luis Pastor (Applied Sciences, 2022)
The city of Chone, being situated on the Ecuadorian coast, was affected due to the close-by epicenter of the earthquake of 16 April 2016, which reached a magnitude of Mw 7.8. This catastrophic event presented settlements in the ground, sand boils and land subsidence, being the most damaging in a variety of civil works among these several buildings. The main objective of the current study is to select data using the standard penetration test (SPT) for the evaluation of the probability of liquefaction considering a maximum acceleration seismic risk of amax = 0.5 g. With the tabulated information, a liquefaction hazard map was generated for the city of Chone, where a safety factor of 1228 was obtained, determining the potentially liquefiable strata at an approximate depth between 9 and 11 m. Hereby, we were able to demonstrate results that were obtained experimentally through a quantitative analysis, indicating that the urban area of the city of Chone has a high probability of liquefaction, which was supported due to the presence of Holocene-aged soils developed in alluvial deposits, located in an alluvium mid catchment area. This novel research, due to the combination of a variety of used tools in the seismic risk evaluation, provides a relevant contribution to territorial planning and risk management in construction, in addition to the territorial reorganization of the canton as an example for different regions worldwide with similar geodynamics, soil mechanics and seismic vulnerabilities.